Note su ‘Ḏulfaqār dell’Intelletto’ e il manicheismo islamizzante - Piras, Andrea (Annali di Ca’ Foscari: Serie Orientale, 2023)
The present essay aims at elucidating the imagery of the New Persian fragment in Manichaean script M 786, dealing with the lament of the Anima Viva entrapped in the material world. The poetical text is a remarkable sample of the Manichaean language and its strategy of literary concealing, by means of Islamic and Crypto-Manichaean mixed expressions, such as the ‘Ḏulfaqār of Intellect’, which is related (I suggest) to the Living Spirit. Within this fragment, a series of funerary terminologies have also been employed, denoting the captivity of the Soul into the Matter, to describe the pain of the human existence and the yearning for salvation, provided by the gods.